Clinical Profile and Early Outcomes of Minimally Invasive Cardiac Surgery: A Cross-Sectional Study from a Tertiary Center in Pakistan - Muhammad Yasir Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Minimally invasive cardiac surgery (MICS) has emerged as a viable alternative to conventional sternotomy-based procedures. Its adoption is growing due to advantages such as reduced surgical trauma, shorter recovery, and fewer complications. However, limited data are available from low-resource settings like Pakistan. Objective: To evaluate the early clinical outcomes of patients undergoing MICS in a tertiary cardiac center in Pakistan. Methods: This descriptive cross-sectional study included 160 patients who underwent MICS at Mukhtar A Sheikh Hospital, Multan, between February 2023 and February 2023. Procedures included MIDCAB, minimally invasive valve surgeries, and ASD closures. Patient demographics, intraoperative findings, and early postoperative outcomes were analyzed using descriptive statistics. Results: The mean patient age was 53.4 ± 8.5 years, with a mean ejection fraction of 56.2%. Most patients (72%) underwent CABG via MICS approach. The average hospital stay was 5.7 days. Blood products were used in 52% of cases. The mean postoperative ventilation time was 10.1 hours, and the mean chest drainage was 645 mL. Conclusion: MICS in a resource-limited environment shows favorable early outcomes with short ICU and hospital stays, low blood product requirements, and preserved cardiac function. These findings support broader implementation of MICS techniques in similar clinical settings. Keywords: Minimally invasive cardiac surgery, CABG, valve surgery, early outcomes, Pakistan, resource-limited setting